Determination of Preventive Maintenance Interval Based on Reliability Threshold and Risk-Based Maintenance - Gilang Maulana Akbar; Annisa Kesy Garside; Rahmad Wisnu Wardana (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret (UNS), 2026)
PT. XYZ is a company engaged in sugar production, where the cane cutter machine plays a critical role in shredding sugarcane before extraction. During the milling period from May to November 2023, the machine experienced 31 breakdowns, leading to considerable downtime and increased operational costs. This study determines maintenance intervals using the Risk-Based Maintenance (RBM) approach to assess risk levels and the Cost of Unreliability (COUR) method to quantify financial impacts. The initial RBM analysis identified a monthly risk value of IDR 47,147,150. By implementing scheduled replacement intervals—17 days for the cutting knife, 28 days for the cutting disk, 14 days for the bearing, 31 days for the conveyor, and 26 days for the driving turbine—the Cost of Reliability (COR) was established at IDR 76,700,415/month. Although the planned expenditure increased, it remains within the company's 2% tolerance limit at a 1.66% severity level. Furthermore, the COUR analysis revealed that the potential downtime loss of IDR 238,583,981 far outweighs the preventive investment. These results demonstrate that integrating RBM and COUR methods effectively balances maintenance costs while protecting the company from disproportionate financial losses due to equipment unreliability.